94.1k views
0 votes
Simplify: (3n2 +9+5n4 – 3n)+(-9n* - 7 -5n?)

User Oldbam
by
5.2k points

1 Answer

6 votes

Answer:

3n^2+9+5n^4+55n

Explanation:

Steps

$\left(3n^2+9+5n^4-3n\right)+\left(-9n\left(-7\right)-5n\right)$

$\mathrm{Remove\:parentheses}:\quad\left(a\right)=a,\:-\left(-a\right)=a$

$=3n^2+9+5n^4-3n+9n\cdot\:7-5n$

$\mathrm{Add\:similar\:elements:}\:-3n-5n=-8n$

$=3n^2+9+5n^4-8n+9\cdot\:7n$

$\mathrm{Multiply\:the\:numbers:}\:9\cdot\:7=63$

$=3n^2+9+5n^4-8n+63n$

$\mathrm{Add\:similar\:elements:}\:-8n+63n=55n$

$=3n^2+9+5n^4+55n$

User Klyd
by
6.0k points